Hábitos de higiene en los mercados de mayor abastecimiento de carnes en la Ciudad de Huánuco en la relación a la contaminación bacteriológica 2013 - Escobedo Bailón, Christian (2017)
The objective of the research was to determine the influence of health habits during marketing in the bacterial contamination of red and white meat in the food markets of our city. It was conducted a descriptive study cross-sectional observation, with 105 retailers and meat samples from markets of Huanuco department and Paucarbamba district during the period 2009. It was used a survey and observation files to gather data. For the inferential analysis of the results was used X2 Square Test and Pearson’s correlation coefficient. To determined that 63.8% of meat samples were positive for Escherichia coli, Enterobacter aerogenes also it was found (29.5%), Staphylococcus aureus (18.1%), Klebsiella sp (15.2%), Citrobacter freundii (17.1%), Bacillus subtilis (11.4%) and Bacillus cereus (8.6%). The analysis reveals a high level of bacterial contamination, an unacceptable sanitary conditions (55.2%), sensory rejection condition (57.1%) and the average pH decreased (4.77), and relate them were statistically significant with p <0.05. Finally the conclusions where that the food markets of Huanuco and Paucarbamba recorded poor sanitary conditions and high bacterial contamination, it is necessary to establish preventive and control measures against the risk it represents to public health.